NEYROPEDAGOGIK YONDASHUVLAR ASOSIDA OLIY TA‘LIMDA MOTIVATSIYANI OSHIRISHNING PSIXO-BIOLOGIK MEXANIZMLARI - O‘ktamova Shahrizoda Shavkatovna (TADQIQOTLAR, 2025)
Abstract. This article scientifically and theoretically analyzes the psychobiological mechanisms of increasing students’ motivation for learning in higher education based on neuropedagogical approaches. The study highlights the importance of brain activity, emotional state, attention processes, and the dopamine system in the learning process, and shows the role of neurophysiological factors in the formation of motivation. It also substantiates the effectiveness of neurodidactic methods that enhance cognitive activity in students, multimodal educational technologies, psychological training that reduces stress, and educational strategies adapted to individual neurotypes. The article is aimed at improving scientific and methodological approaches to increasing motivation in the higher education system and explores the possibilities of sustainable development of students’ learning activity.